Potential of Metal Minerals in the Weikeri River, North Wetar, and Southwest Maluku - Arif, Subhan; Dzakiya, Nurul; Tuheteru, Maulana Mairatu (Politeknik Negeri Batam, 2023)
The modern era, demand for metals as raw materials in technology continues to increase along with industrial development. Metals are used in various sectors, such as construction, automotive, electronics, and renewable energy. However, the availability of currently used metals is limited and poses challenges in terms of supply and environmental impact. To overcome these limitations, it is important to search for new metal resources. The potential for the existence of new metal deposits can be discovered through comprehensive geological research, especially in areas that have not been widely explored. One area of interest for this research is the Weikeri River, Uhak Village, Southwest Maluku. This research aims to explore the potential for metal deposition in the Weikeri River area and Uhak Village, Southwest Maluku. Using surface geological survey techniques, this research was carried out through a literature study stage and then a field geology study. Field studies are aimed at obtaining lithology, geological structure, alteration, and mineralization data. The results of field research show that the research location is composed of underwater volcanic rocks. Rock alteration conditions are dominated by the propylitic alteration type in andesite lithology, both in lava and in intrusions in the form of dikes and sills. Other alterations are argillic and silicified. The mineralization condition found was a brecciated quartz vein system. The resulting minerals found were sulfide minerals in the form of pyrite, galena, and chalcopyrite. The percentage of the presence of these minerals ranges from 1–3% on the surface.